Study of the antiulcer properties of extracts obtained from the fruit of the domestic plum (Prunus Domestica L.) - Galuzinska, Liubov; Seniuk, Igor; Kravchenko, Vira; Naboka, Olga (ScienceRise: Biological Science, 2025)
Aim. To search for and select an effective dose of plant extracts with anti-ulcer activity, obtained from the fruits of Prunus domestica L. (family Rosaceae, cultivar "Ugorka"), which are widely cultivated in Ukraine as a fruit-berry crop. Materials and Methods. For the experimental investigation of the anti-ulcer activity of the extracts under study and the comparative drug ranitidine, two models were chosen, in which ulcers were induced on the gastric mucosa by an ethanol-prednisolone mixture and by indometacin solution. Against the background of the model pathology, biomarkers were measured in gastric homogenate and in blood serum: lipid peroxidation (LPO), thiobarbituric acid reactive substances (TBARS), diene conjugates (DC), and reduced glutathione (GSH). The degree of ulcer defect was assessed visually using a 5-point scale. Results. Under the ethanol-prednisolone ulcer model in rats, after administration of the extract PEF at a dose of 200 mg/kg, a reduction in the degree of ulcer defect by 36.6 % was observed; inhibition of the LPO process was accompanied by a decrease in serum DC by 1.4-fold, TBARS by 1.8-fold, and an increase in GSH by 1.2-fold. In the gastric homogenate, a significant increase in GSH by 1.4-fold and a decrease in DC and TBARS by 1.4-fold were also observed. The extract PEPC at 200 mg/kg was also effective in this ulcer model, with anti-ulcer activity of 31.8 %, confirmed by normalization of biochemical parameters in serum and gastric homogenate. A marked anti-ulcer effect was also observed in the indometacin ulcer model and was confirmed by a significant reduction in ulcer formation by 1.4-fold and 1.5-fold, respectively, when treated with PEF extract at doses of 100 and 200 mg/kg compared to animals in the control group. A statistically significant enhancement of antioxidant defense in gastric homogenate (1.2-fold) and liver homogenate (1.3-fold) was noted at 100 mg/kg, and 1.4-fold at 200 mg/kg. The administration of PEPC extract at doses of 100 and 200 mg/kg in the indometacin ulcer model positively affected the general condition of the animals and reduced the degree of damage to the gastric mucosa (GSM). There was inhibition of LPO processes, evidenced by statistically significant decreases in TBARS in gastric homogenate (1.3-fold and 1.5-fold, respectively) and liver (1.4-fold). A significant increase in antioxidant defense was also detected in gastric homogenate (1.3-fold) and liver homogenate (1.4-fold) at 100 mg/kg and 1.5-fold at 200 mg/kg. Conclusions. In the conditions of experimental gastric ulcers in animals, treated with the PEF and PEPC extracts, moderate anti-ulcer properties were observed, although they were inferior to the comparative drug ranitidine. It has been demonstrated that the PEF and PEPC extracts inhibit the course of LPO reactions and support endogenous antioxidant defense systems